2017
DOI: 10.1097/tp.0000000000001314
|View full text |Cite
|
Sign up to set email alerts
|

Increased Frequency of BK Virus-Specific Polyfunctional CD8+ T Cells Predict Successful Control of BK Viremia After Kidney Transplantation

Abstract: Background BK virus infection remains an important cause of loss of allograft function after kidney transplantation. We sought to determine whether polyfunctional T cells secreting multiple cytokines simultaneously, which have been shown to be associated with viral control, could be detected early after start of BK viremia, which would provide insight into the mechanism of successful antiviral control. Methods Peripheral blood mononuclear cells collected during episodes of BK viral replication were evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 23 publications
1
28
1
Order By: Relevance
“…A more effective antiviral cellular response may explain improved SV40T tissue鈥恈learance rates and amelioration of the activity of tubular destruction when interstitial mononuclear cells were present. The concept of an ultimately beneficial mononuclear cell response in BKVAN is supported by other studies of antiviral inflammation . The causal relationship between inflammatory cells and parenchymal tubular damage appeared to be bidirectional and complex.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…A more effective antiviral cellular response may explain improved SV40T tissue鈥恈learance rates and amelioration of the activity of tubular destruction when interstitial mononuclear cells were present. The concept of an ultimately beneficial mononuclear cell response in BKVAN is supported by other studies of antiviral inflammation . The causal relationship between inflammatory cells and parenchymal tubular damage appeared to be bidirectional and complex.…”
Section: Discussionmentioning
confidence: 73%
“…Antigen鈥恠pecific T cells can recognize nonstructural (small t and large T) antigenic targets and virus capsid proteins (VP1, VP2, and VP3) . In early BK viremia, circulating CD4 + T helper and T cytotoxic cells and specific polyfunctional CD8 + T cells are detectable. Virus鈥恠pecific lymphocyte clones infiltrate into infected kidneys, classified by next鈥恎eneration sequencing of TCRs following ex vivo BK or allospecific HLA peptide stimulation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that in KTRs, reconstitution of BKV-specific T cells is associated with better control of viruria and viremia (8,71,(77)(78)(79)(80)(81). These studies indicate that immune control is dependent on both CD4 烯 and CD8 烯 T cells (82) and correlates with the frequency of polyfunctional BKV-specific T cells (83). This suggests that monitoring the frequency of BKV-specific T cells following transplantation may provide a strategy to predict the risk of viral reactivation and BKVAN, as shown previously for T cell responses to human cytomegalovirus (CMV) in transplant recipients (84).…”
Section: Adaptive Immune Responsementioning
confidence: 90%
“…24 Patients with more polyfunctional CD8+ T cells expressing multiple cytokines were more likely to clear BK infections within 3 months. 25 Bohl et al studied urine samples from 20 recipient pairs of a deceased kidney transplant. Each of these pairs received 2 kidneys from the same deceased donor.…”
Section: Epidemiologymentioning
confidence: 99%